IP3 receptor depletion in a spontaneous canine model of Charcot-Marie-Tooth disease 1J with amelogenesis imperfecta. - Marjo K Hytönen; Julius Rönkkö; Sruthi Hundi; Tarja S Jokinen; Emilia Suonto; Eeva Teräväinen; Jonas Donner; Rita La Rovere; Geert Bultynck; Emil Ylikallio; Henna Tyynismaa; Hannes Lohi (PLoS Genetics)
Inositol 1,4,5-trisphosphate receptors (IP3R) mediate Ca2+ release from intracellular stores, contributing to complex regulation of numerous physiological responses. The involvement of the three IP3R genes (ITPR1, ITPR2 and ITPR3) in inherited human diseases has started to shed light on the essential roles of each receptor in different human tissues and cell types. Variants in the ITPR3 gene, which encodes IP3R3, have recently been found to cause demyelinating sensorimotor Charcot-Marie-Tooth neuropathy type 1J (CMT1J). In addition to peripheral neuropathy, immunodeficiency and tooth abnormalities are occasionally present. Here, we report the identification of a homozygous nonsense variant in the ITPR3 gene in Lancashire Heeler dogs, presenting with a severe developmental enamel defect and reduced nerve conduction velocity. We studied the primary skin fibroblasts of the affected dogs and observed that the nonsense variant in ITPR3 led to a complete absence of full-length IP3R3 protein. Unexpectedly, the protein levels of IP3R1 and IP3R2 were also markedly decreased, suggesting co-regulation. Functional Ca2+ measurements revealed reduced IP3R-mediated Ca2+ flux upon stimulation of G-protein-coupled-receptors in the affected dog fibroblasts. These findings highlight the first spontaneous mammalian phenotype caused by a nonsense variant in ITPR3, leading to the loss of IP3R3. The human and canine IP3R3 proteins are highly similar, and our study suggests that the tissue involvement resulting from the receptor's dysfunction is also conserved. In summary, IP3R3 is critical for enamel formation and peripheral nerve maintenance.